Goalkeepers' rating, evaluation and classification, according to the number of games, participation time and effectiveness at the Women's European Handball Championship in 2018. (4th July 2019) - Hatzimanouil, Dimitrios
ABSTRACT: Nowadays there is a rapid growth in female handball but little research data. This study aimed to rate, evaluate and classify the goalkeepers according to the number of games, participation time and effectiveness of 33 female goalkeepers during Women's European Championship (2018). The variables were the throws received by the goalkeepers and the saves they made. Based on criteria goalkeepers were categorised into three categories of performance: Class A, Class B and Class C. The method applied was descriptive and inferential statistics. The Kruskal–Wallis test was used to compare the differences among the three performance classes. The Mann–Whitney U test was applied to compare the differences among the three performance classes for the aforementioned variables. The final ranking of the 33 goalkeepers, differed from the official ranking. Kruskal–Wallis analysis revealed significant differences among the classes A, B and C (p < 05). Mann–Whitney U test revealed that Class A differed significantly from B and C classes (p < 05). Class B differed significantly from Class C (p < 05). In conclusion, in order to rate goalkeeper's performance, not only the effectiveness should be measured, but also the number of games and the exact playing time.